Effect of pH on the Electrochemical Redox Behavior of Co2+ in Acetate Buffer Solution - Kabir, Ahsanul; Yeasmin, Humaira; Hasan, Md Abu; Rahman, MS; Hoque, MA; Bakshi, Pradip K; Shaikh, AA (Dhaka University Journal of Science, 2017)
The electrochemical redox behavior of transition metal ion Co2+ at different pH in acetate buffer solution has been investigated using cyclic voltammetry and differential pulse voltammetry at glassy carbon electrode (GCE). In cyclic voltammograms (CVs), Co2+ shows a pair of cathodic and a pair of anodic peak. The peak potential separation and peak current ratio reveals that the redox process of the redox couples, Co2+/Co+ and Co+/Co followed a quasi-reversible behavior and are two step one-electron transfer processes. The electrochemical processes are diffusion controlled. The nature of CV of Co2+ has greatly influenced by the potential scan rate and solution pH. With increasing scan rate both cathodic peaks shifted towards negative potential and first cathodic peak was eventually diminished. In the reverse direction, unexpected behavior such as distinguishable second anodic peak, identical heights of two anodic peaks, three humps like peaks and finally domination of second anodic peak were noticed. However, in lower pH all the above mentioned behavior appeared with higher scan rate. While at higher pH of the solution the peculiar behavior was found at lower scan rate. Nevertheless, at pH 6.5, it demonstrated intense cathodic peaks and a very large anodic peak at all scan rates. Dhaka Univ. J. Sci. 65(2): 107-112, 2017 (July)